Synergy Panorama of the Doctoral Process (UNWE Yearbook, 2023)
There is a set of problems that emerges before the contemporary organization of the doctoral studies in economic sciences and their resolution is determined by the factors of employing the systemic, cybernetic and synergy approach. Evolution and catastrophic leap are the two paths of contemporary development that are based on the richness of scientific insight. Its grounds are laid in the field of doctoral studies as the starting phase of each science. The object of this piece of research is the doctoral process, while its research topic is the latter’s synergy panorama. A basic assumption held is that the synergistic reflection should be interpreted as the dictatorship of the integrity of the examined process. In its standard form, the interrelated behaviour of self-organization is interpreted in terms of hierarchization (obedience), parameters of order (order and chaos), cyclical reason (obligatory feedback) that are all targeted at establishing a natural order in doctoral studies – self-sufficiency with the presumption of growth.